Analysis of Early Childhood Education Practic - Farah Naz , Amna Yousaf, Naeem Arshad (JECCE, 2023)
This study aimed at analysis of ECE practices in education at school level. The goal of this study was to investigate the ECE amenities, current does &don’ts and discovering the prevailing position of ECE in government and other schools in Pakistan. This level of education influences the whole life of every individual in his/her academic and non-academic achievements. This is also the basic stage to improve the literacy rate of future leaders so that children can enter in schools of our society successfully. The population of the study was all teachers of ECE from schools of both segments. The number of total respondents was 200 (Public= 100, private=100). Convenience sampling was used by selecting model town Tehsil of Lahore. Adopted questionnaire was used to collect the data from respondents. Fifty questions were used to collect data in the questionnaire. The finding of the study concludes that there was no significant difference between public and private pre-schools.